The Effect of Shopee Ads, Shopee Vouchers and Customer Reviews on Consumer Decisions for Make Over Cosmetic’s at Shopee - Usna, Nisaul; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2025)
Researh Aim : This study seeks to examine the impact of Shopee Ads, Shopee Vouchers, and customer reviews on consumer decisions for Make Over products on Shopee. Design/Methodology/Approach : This research uses a quantitative approach with causality techniques. Data was collected through questionnaires from 40 respondents selected by purposive sampling method. Data analysis was carried out using multiple linear regression tests. Reseacrh Finding : The research showed that Shopee Ads, Shopee Vouchers and customer reviews significantly influenced consumer decisions both partially and simultaneously. These three factors play an important role in influencing consumer decisions to buy make over products at Shopee Theoretical Contribution/Originality : This research makes a theoretical contribution by enriching the literature on the effectiveness of digital promotional tools in the context of e-commerce, especially on the variables Shopee Ads, Shopee Vouchers, and customer reviews. Pratical/Policy Implications : The findings of this study provide guidance for businesses to maximize promotions through Shopee Ads and Shopee Vouchers and maintain positive customer reviews. This strategy can increase consumer loyalty and product competitiveness in the marketplace Research Limitations : This research has limitations on a small sample size and focuses on one e-commerce platform, namely Shopee. Further research could include other platforms to understand the different effectiveness of digital promotional tools